Floristic diversification of spreading liverseed grass pasture according to different cutting intensities, obtained by grazing simulation - Marchi, Sidnei Roberto de; Marques, Ricardo Fagundes; Souza, Rodrigo Marques de; Araújo, Prissila Pereira dos Santos; Silva, Ilgner Thiago Duarte (Acta Scientiarum. Animal Sciences, 2021)
This study aimed to evaluate the impacts of different forage cutting intensities, obtained by grazing simulation, on the floristic diversity and productivity of a pasture cultivated with spreading liverseed grass. The experiment was set up in a randomized block design, with four replications and treatments arranged in a 5 × 2 factorial scheme, with five levels of cutting intensity of the simulated grazing (0, 25, 50, 75, and 95% of the forage canopy) associated with two levels of weed coexistence (presence and absence). The evaluations of floristic diversity, number of individuals, and total dry matter of weeds were obtained at 15, 30, 45, 60, and 90 days after grazing simulation (DAGS). All plots were evaluated at the end of the experimental period (90 DAGS) for the amount of dry biomass produced by the pasture. The results showed that higher forage cutting intensities, obtained by grazing simulation, increased the floristic diversity, the number of individuals, and the dry matter accumulated by weeds in a pasture grown with spreading liverseed grass, reducing by up to 56% the production of total dry matter of the forage.